Quality of Continuing Engineering Education: DAETE and EFQM - Soeiro, Alfredo (International Journal of Advanced Corporate Learning (iJAC), 2020)
DAETE was a project created to develop accreditation procedures to ensure quality of continuing engineering education (CEE) courses. Financed by the European Commission and by the USA government it was adapted to evaluate and to improve quality of the centres in both sides of the Atlantic to foster recognition and cooperation. Among the several quality management models available in the academic and industrial contexts the partnership chose EFQM. The model was developed in two years with four partners from Europe and one from the USA. The development consisted in the adaptation of the EFQM descriptors to the specific contexts of CEE centres. Issues like dimension of centres, relevant results, processes relevant for the goals and appropriate indicators were thoroughly discussed and defined. During the years that followed the implementation and validation occurred with similar financing and with the participation of about one hundred centres around the world. The analysis of the implementation of the modified EFQM variant in several contexts is made in this paper and conclusions are presented. The conclusions also include recommendations for the adoption of the EFQM model to organizations involved in education and training.